2011
DOI: 10.7150/ijms.8.88
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Nonstructural Protein-Induced Damage of Cellular DNA and Resultant Apoptosis

Abstract: Parvovirus B19 is a widespread virus with diverse clinical presentations. The viral nonstructural protein, NS1, binds to and cleaves the viral genome, and induces apoptosis when transfected into nonpermissive cells, such as hepatocytes. We hypothesized that the cytotoxicity of NS1 in such cells results from chromosomal DNA damage caused by the DNA-nicking and DNA-attaching activities of NS1. Upon testing this hypothesis, we found that NS1 covalently binds to cellular DNA and is modified by PARP, an enzyme invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Studies have been shown NS1 covalently binds to cellular DNA and is modified by PARP (Poly ADP ribose polymerase), an enzyme involved in repairing single-stranded DNA nicks. The DNA nick repair pathway initiated by PARP and the DNA repair pathways initiated by ATM/ATR are necessary for efficient apoptosis resulting from NS1 expression (Poole et al, 2011;Momoeda et al, 1994). NS1-induced apoptosis was inhibited by caspase 3, 6, and 8 inhibitors, and substantial caspase 3, 6, and 8 activities were induced by NS1 expression.…”
Section: Functional Genomics Of the B19 Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been shown NS1 covalently binds to cellular DNA and is modified by PARP (Poly ADP ribose polymerase), an enzyme involved in repairing single-stranded DNA nicks. The DNA nick repair pathway initiated by PARP and the DNA repair pathways initiated by ATM/ATR are necessary for efficient apoptosis resulting from NS1 expression (Poole et al, 2011;Momoeda et al, 1994). NS1-induced apoptosis was inhibited by caspase 3, 6, and 8 inhibitors, and substantial caspase 3, 6, and 8 activities were induced by NS1 expression.…”
Section: Functional Genomics Of the B19 Virusmentioning
confidence: 99%
“…The NS1-specific T cells provide the helper signal required, in addition to the DNA signal, for the anergized B cell to break tolerance. vDNA = viral DNA; hDNA = human DNA; TC = T cell receptor; PS receptor = phosphatidylserine receptor; FcR = Fc receptor (Poole et al, 2011). The life cycle of parvovirus B19 includes binding of the virus to host cell receptors (1), internalization (2), uncoating and translocation of the genome to the host nucleus (3), DNA replication (4), RNA transcription (5), protein translation (6), assembly of capsids and packaging of the genome (7), and finally cell lysis with the release of the mature virions (8).…”
Section: Figmentioning
confidence: 99%
“…Some studies have hypothesized that PVB19 induced autoimmunity may occur when T cells specific for NS1 protein are stimulated during a reoccurrence of PVB19 infection or restimulation of NS1 expression; NS1 protein specific T lymphocyte helper cells would then provide second signal to anergized autoantigen specific B lymphocytes [16,17]. Thammasri, in an experimental study, showed that apoptotic bodies (including potential self-antigens associated in autoimmunity such as Smith, ApoH, DNA, histone H4 and phosphatidylserine) can be generated by PVB19 NS1 expression in a non-permissive cell line [18].…”
Section: Cellular Autoimmunitymentioning
confidence: 99%
“…The S phase arrest is an outcome of accumulation of DNA damage, which is indispensable for B19 as well as B19 NS1-mediated induction of apoptosis in non-permissive mammalian cells [79]. This event has been attributed to the nicking ability of NS1 directed at the cellular DNA, causing accumulation of DNA damage, which is evident by the activation of poly (ADPribose) polymerase (PARP) [79,80].…”
Section: Ns1 Of Rat Parvovirus H-1pv (H-1pv Ns1)mentioning
confidence: 99%
“…In non-permissive cells, B19 NS1, through its endonuclease domain, causes chromosomal DNA damage and activation of repairing proteins, leading to the induction of apoptosis [79,80,84]. Unlike permissive cells, apoptosis in non-permissive cell lines seems to follow the intrinsic or mitochondrial pathway as evidenced by the up-regulation of pro-apoptotic protein Bax and activation of caspase 9 and 3, but not caspase 8 [81,85,86].…”
Section: Ns1 Of Rat Parvovirus H-1pv (H-1pv Ns1)mentioning
confidence: 99%